HUBUNGAN ANTARA KUALITAS TIDUR DAN INDEKS MASSA TUBUH DENGAN DENYUT JANTUNG ISTIRAHAT PADA MAHASISWA KEDOKTERAN FAKULTAS KEDOKTERAN UPN "VETERAN" JAKARTA - Audhry Aulia Hasna (2023)
Resting heart rate (RHR) is the number of heartbeats at rest. It can be associated with the incidence and mortality of cardiovascular and non-cardiovascular diseases. Several factors which can affect RHR are sleep quality, body mass index (BMI), and blood pressure (BP). Sleep quality in medical students tends to be poor which lead to increase in RHR. Underweight, overweight and obesity incidence also continues to increase in Indonesia. An increase in BMI can lead to increase in RHR. People with hypertension tend to have high RHR. This study aims to determine the relationship between sleep quality, BMI, and BP on RHR in female students of Faculty of Medicine UPN "Veteran" Jakarta. This study was an analytic cross-sectional study involving 90 pre-clinical students. The sampling methods uses simple random sampling. Respondents were given Pittsburgh Sleep Quality Index (PSQI) questionnaire, BP and RHR was measured using Omron HEM-6181. Data were analyzed using the chi-square. The results show that the majority of respondents have poor sleep quality (73,3%), normal BMI (28,9%), low BP (76,7%), and high RHR (54,4%). It shows that there is relationship between sleep quality and BMI with RHR (p=0.005, p=0,004), but no relationship between BP and RHR (p=0,611). Conclusion: There is a relationship between sleep quality and BMI with RHR in female students at the Faculty of Medicine UPN "Veteran" Jakarta, but no relationship between BP and RHR. Poor sleep quality and excessive BMI tend to cause DJI to increase which is caused by increased sympathetic nervous activity.